2013
DOI: 10.1074/jbc.m113.462804
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serpin Determinants of Specificity and Selectivity for Furin Inhibition through Studies of α1PDX (α1-Protease Inhibitor Portland)-Serpin B8 and Furin Active-site Loop Chimeras

Abstract: Background: ␣ 1 -Protease inhibitor Portland (␣ 1 PDX) and serpin B8 are proprotein convertase (PC) inhibitors whose specificity and selectivity for PCs are not understood. Results: ␣ 1 PDX-serpin B8 and furin-PC chimeras revealed new serpin and protease (re)active-site and exosite determinants of reactivity. Conclusion: ␣ 1 PDX reactive-site and exosite determinants may be exploited for engineering specificity and selectivity for inhibiting PCs. Significance: Specific PC inhibitors will advance understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(50 citation statements)
references
References 32 publications
(39 reference statements)
0
50
0
Order By: Relevance
“… also reported that cathepsin L degrades filaggrin but serpin B13 (Hurpin) as does serpin B3 inhibits it, which may be mitigating filaggrinolysis . Furin, a member of the subtilisin/kexin‐like mammalian proprotein convertases, is also involved the (pro)filaggrin processing and its inhibitor serpin B8 is increased in the cheek samples which may account for the lack of total (pro)filaggrin processing on the cheek compared with the PA site . The UCA and PCA generating enzymes, histidine ammonia‐lyase (3×) and gamma‐glutamyl cyclotransferase, respectively, were also increased together with arginase‐1 (3×), that contributes to urea formation .…”
Section: Discussionmentioning
confidence: 99%
“… also reported that cathepsin L degrades filaggrin but serpin B13 (Hurpin) as does serpin B3 inhibits it, which may be mitigating filaggrinolysis . Furin, a member of the subtilisin/kexin‐like mammalian proprotein convertases, is also involved the (pro)filaggrin processing and its inhibitor serpin B8 is increased in the cheek samples which may account for the lack of total (pro)filaggrin processing on the cheek compared with the PA site . The UCA and PCA generating enzymes, histidine ammonia‐lyase (3×) and gamma‐glutamyl cyclotransferase, respectively, were also increased together with arginase‐1 (3×), that contributes to urea formation .…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach could be used for tick serpins, where the reactive center loop (RCL), which is responsible for serpin specificity, would be of tick origin, and the conserved serpin scaffold would be of human origin (Silverman et al, 2010; Whisstock et al, 2010). The concept of creating novel serpins by combining the RCL and scaffold from different serpins has been proven with the fusion of the furin inhibitor B8 and the mutant variant of α1-antitrypsin (Izaguirre et al, 2013, 2019). Furthermore, a novel extracellular inhibitor of human granzyme B was produced by combining mouse RCL and a human scaffold into a single chimera (Marcet-Palacios et al, 2015).…”
Section: Tick Proteins and Bioengineeringmentioning
confidence: 99%
“…143,144 However, transplanting the P6-P1 RCL residues from the natural furin inhibitor Serpin B8 into α 1 -AT improved the rate of furin inhibition twofold versus α 1 -PDX, and surprisingly 10-fold versus the original Serpin B8. 145 Selectivity toward other proprotein convertases could be tuned via additional mutations, by introducing P 0 RCL residues from Serpin B8 or Serpin B8 exosite residues. 146 α 1 -AT, therefore, appears to be an attractive and tunable scaffold for engineering inhibitors of a variety of proprotein convertases.…”
Section: Inhibition Of Other Proteinasesmentioning
confidence: 99%